Real-World Treatment Outcomes of an Artificial Tear Containing Arabinogalactan, Hyaluronic Acid and Trehalose Among Subjects with Dry Eye - Bedei A; Rocha Cabrera P; Oliveira L; Castellini L; De Grazia G; Remiddi S (Clinical Ophthalmology)
Andrea Bedei,1 Pedro Rocha Cabrera,2 Luis Oliveira,3 Laura Castellini,1 Giulia De Grazia,4 Stefano Remiddi4 1Ophthalmology Department Casa di Cura San Camillo, Forte dei Marmi, Italy; 2Ophthalmology Department Hospital San Juan de Dios Tenerife, Santa Cruz de Tenerife, Spain; 3Ophthalmology Department Hospital Santo Antonio, Porto, Portugal; 4Department of Research and Development, MD Italy, Albano Laziale, ItalyCorrespondence: Stefano Remiddi, MD Italy srl, Department of Research and Development, Via Cancelliera, 12, Albano Laziale, Rome, 00041, Italy, Email stefano.remiddi@md-italy.itPurpose: To assess the efficacy, adherence, and tolerability of a new artificial tear based on arabinogalactan, hyaluronic acid, and trehalose in a population with dry eye disease (DED).Methods: A retrospective, real-world, post-marketing study identified 96 adult patients (aged 18– 80 years) with signs and symptoms of dry eye. These patients received fixed combination therapy with eye drops containing arabinogalactan, hyaluronic acid, and trehalose at various dosing schedules. The data for this study were collected from April 2022 to June 2023. Patients underwent evaluation at baseline (T0) and after a follow-up period of two–three months (T1) using a patient-reported questionnaire.Results: In 96 adult patients (71 women and 25 men) with dry eye due to various conditions, the results indicated a 98% positive response to therapy. This response included improvements in vision (13%), comfort (39%), redness (13%), itching (16%), photophobia (4%), and tearing (14%). Additionally, 61% of the patients experienced 1– 2 hours of comfort following instillation.Conclusion: This real-life post-marketing study demonstrated clinical improvement of signs and symptoms in patients with dry eye disease using a new artificial tear medical device based on arabinogalactan, hyaluronic acid, and trehalose.Keywords: dry eye, real-world study, arabinogalactan, hyaluronic acid, trehalose, post-marketing study